A teoria do roteiro como possibilidade metodológica para o ensino de história - D’Avila, Yasmin Daniella (2024)
This master's research has as its central theme the teaching of local history. Starting from my reality as a teacher in the municipality of Santa Cruz do Sul (RS), I propose a pedagogical intervention based on the research problem “how the Script Theory presents itself as a methodological possibility for the teaching-learning of Local History that values multiple narratives?” To this end, I created a booklet that highlights the intervention proposal for teaching local History, the final product of this research, using Documentary Theory based on the ideas of screenwriter Syd Field, designed and adapted for High School. To support this discussion, I depart from the theoretical perspective of decolonial and countercolonial studies, problematizing the importance of telling other stories about the constitution of localities, which can interrogate hegemonic narratives and involve students in a study of their realities as historical subjects. The proposition was also used in the classroom during a teaching practice with a 2nd year high school class at a state school. Observations about the practice were analyzed and it was possible to conclude the feasibility of its application.